2016
DOI: 10.1364/ol.42.000135
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurement of the topological charge of a perfect vortex using the phase shift method

Abstract: We propose a method to determine the topological charge (TC) of a perfect vortex. With the phase shift technique, the perfect vortex and its conjugate beam exactly overlap and interfere. Consequently, the TC of a perfect vortex is determined by counting the number of interference fringes. This proposed method enables in situ determination of the TC of the perfect vortex without the need for additional optical elements, and it is immune to environmental vibration and parasitic interference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…proposed the concept of “perfect optical vortex” (POV), whose bright ring radius is independent of the TCs. Subsequently, POV generation methods and properties were studied in detail in some studies . Further, POV lattices were generated to different n th diffraction orders of the spatial light modulator (SLM), which represents the magnitude and sign of the TC of each POV .…”
Section: Introductionmentioning
confidence: 99%
“…proposed the concept of “perfect optical vortex” (POV), whose bright ring radius is independent of the TCs. Subsequently, POV generation methods and properties were studied in detail in some studies . Further, POV lattices were generated to different n th diffraction orders of the spatial light modulator (SLM), which represents the magnitude and sign of the TC of each POV .…”
Section: Introductionmentioning
confidence: 99%
“…Where, the annular spiral phase (liθ+αr) can realize to offset radially the optical vortex by radial shift factor α (i.e., the optical vortex shrinks for α>0 or expands for α<0). [ 30 ] Superimposing an equiphase ( γ ) over the annular spiral phase is equivalent to a vortex beam interfering with a reference beam, [ 30 ] resulting in an annular twisting lobes intensity pattern, as shown in Figure 3b1. Consequently, the role of an equiphase is regarded as a reference Gaussian beam.…”
Section: Theorymentioning
confidence: 99%
“…However, it seems that the diffraction methods [26]- [28] used to measure the TCs of the ordinary OV are not suitable for the POV. This is because, during the generation of the POV, it appears only in the near proximity of the Fourier plane of a spatial light modulator (SLM) [29]. Therefore, a traditional method is used to measure the TCs of the POV by the interference between a POV beam and a spherical beam [30], [31], but this method requires some specialized optical components with fine alignment and the accuracy of the experimental optical path.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a traditional method is used to measure the TCs of the POV by the interference between a POV beam and a spherical beam [30], [31], but this method requires some specialized optical components with fine alignment and the accuracy of the experimental optical path. To address this problem, Ma et al reported an improved method to measure the POV beam with phase shift technique [29], which can overlap and interfere exactly between the POV beam and its phase conjugate in an approximately Fourier plane. This method can determine the TCs of a POV with simple and non-precise optical elements, but its energy efficiency is relatively low and it even has severe distortions of far-field intensity patterns when measuring the high-order POV beam.…”
Section: Introductionmentioning
confidence: 99%